Nuclear qualification of electrical equipment: challenges for the Brazilian industry - João Manoel Losada Moreira (Brazilian Journal of Radiation Sciences, 2021)
The nuclear industry requires specific safety qualification of electrical equipment in order to assure that they perform their function without experiencing common-cause failures. Electrical equipment used in the nuclear industry have been qualified according to IEEE 323 and IEC 60780 standards and their derivatives until 2016. Currently these two organizations consolidated their requirements and unified them in a common document, the IEC/IEEE 60780-323 standard. It defines the different methods of qualification, a qualification program plan and the documentation to be delivered demonstrating successful qualification of electrical equipment to be used in nuclear installations. Based on this standard, we present an approach focusing on the qualification by type-testing. The article details the necessary tests to be performed for this method, the equipment necessary to be used in the type-testing method and the documentation expected to be delivered by the supplier. To implement this qualification approach and obtain such capacity, it is necessary to perform large expenditures in equipment and in the improvement of the workforce. On the other hand, this capacity gives the companies knowledge, experience and opens new market opportunities in other areas, such as the naval and oil industries. With such expertise, Brazilian companies may become active suppliers in the world industry of electrical equipment.